Socio-Economic Impact of Local Alcohol Consumption by Consumers in Haramaya Town, East Hararghe, Ethiophia - Kersemi Fekadu Teka (Bina Nusantara University, 2019)
The main aim of this research was to assess the socio-economic impact of local alcohol consumption among adult in Haramaya town, East Hararghe, Ethiopia. A community-based cross-sectional study was conducted from April to June 2018 using mixed methods of data collection. A total of 120 samples were included in the research. The most consuming local alcohols were Tell, Katikala, and Tej respectively in the research area. The research found the current prevalence of consuming local alcohol practices was among male sex, productive age groups, followers orthodox church, married respondents, illiterate respondents, and the respondents with low daily income (daily laborers). Besides that, it finds out that consuming local alcohol are leading to different socio-economic problems, such as social problems (discrimination, failure to role play, and low social interaction), economic problems (poverty and lack of saving resources), health problems (headache, vomiting, and loss of appetite), and problems of domestic violence (divorce and lack of proper socialization of their children). Thegovernment with stakeholders should develop a policy to control the production and disruption of local alcohol, as well as develop coping mechanisms for the consumers, producers, and sellers.